2020
DOI: 10.1186/s10020-020-00191-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination of TLR agonist and miR146a mimics attenuates ovalbumin-induced asthma

Abstract: Background microRNA-146a has been reported to be a regulator in the process of attenuating asthma by inhibiting Toll-like receptor 2 (TLR2) pathway. This study aimed to investigate how miR146a-inhibitor affect the symptom of asthma and the underlying mechanisms. Methods Ovalbumin (OVA)-induced allergic asthma mice model was established by intraperitoneal injection with 20 μg of OVA. Total cells and differential inflammatory cells in bronchoalveolar lavage fluid were counted by flow cytometry. The expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…MiRNAs are potential candidates for asthma therapy. For example, miR-146a-5p was reported to efficiently protect mice against OVA-induced allergic asthma ( 32 , 33 ), and also modulate anti-fibrosis responses ( 34 ). Thus, the anti-asthma effects of miR-146a-5p-EVs (Hypo-EVs carrying miR-146a-5p) might be more profound than those of Hypo-EVs.…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are potential candidates for asthma therapy. For example, miR-146a-5p was reported to efficiently protect mice against OVA-induced allergic asthma ( 32 , 33 ), and also modulate anti-fibrosis responses ( 34 ). Thus, the anti-asthma effects of miR-146a-5p-EVs (Hypo-EVs carrying miR-146a-5p) might be more profound than those of Hypo-EVs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that hypoxia culture enhances the anti-inflammatory potency of MSCs in OVA mouse, and miR-146a-5p is critical for these properties [ 18 ]. Apart from modulating anti-inflammatory responses [ 34 , 35 ], miR-146a-5p also has the effect of inhibiting TGF-β1-Smad signaling [ 36 ]. After hUCMSCs were exposed to hypoxia for 24 h, the expression of HIF-1α was increased compared with that of hUCMSC cultured in normoxia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, miRNAs have been shown to be an important beneficial mechanism in the immune microenvironment. Especially, it has been reported that miR-146a-5p could inhibit the proliferation and function (IL-13 secretion) of type II innate lymphoid cells (ILC2), efficiently protect mice against OVA-induced allergic asthma [ 34 , 35 ], and also modulate anti-fibrosis responses induced by TGF-β1-Smad signaling [ 36 ]. The content of miR-146a-5p is relatively abundant in hUCMSC-EVs in accordance with a previous study [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identi ed aberrant miRNA expression pro les associated with asthma severity [9] , or therapy responses [10][11][12] . As a miRNA target gene, LIGHT may be regulated by miR-512-3p, miR-513b-5p, miR-5691, miR-107, miR-140-5p, and miR-17-5p screened by TargetScan.…”
Section: Disscussionmentioning
confidence: 99%